The persistence of atopic dermatitis and filaggrin (FLG) mutations in a US longitudinal cohort - Margolis, David J.; Apter, Andrea J.; Gupta, Jayanta; Hoffstad, Ole; Papadopoulos, Maryte; Campbell, Linda E.; Sandilands, Aileen; McLean, W.H. Irwin; Rebbeck, Tim R.; Mitra, Nandita (Journal of allergy and clinical immunology, 2012)
Atopic dermatitis (AD) is a common skin disease that is characterized by recurrent episodes of itching. Filaggrin (FLG) loss-of-function (FLG null) mutations have been associated with an increased risk of AD. We sought to evaluate the effect of individual FLG null mutations on the persistence of AD over time. We evaluated a multiyear prospective cohort study of children with AD with respect to FLG null mutations (R501X, 2282del4, R2447X, and S3247X). We evaluated the association of these mutations with the persistence of AD symptoms over time with respect to reports of no symptoms of AD and whether topical medication was needed for symptom resolution. Eight hundred fifty-seven subjects were followed for 3684 person-years. One or more FLG null mutations were noted in 16.3% of subjects and specifically in 27.5% of white subjects and 5.8% of African American subjects. Subjects with an FLG null mutation were less likely (odds ratio [OR], 0.54; 95% CI, 0.41-0.71) to report that their skin was symptom free at any time compared with those without an FLG null mutation. The effect of these mutations was similar in white subjects (OR, 0.42; 95% CI, 0.31-0.57) and African-American subjects (OR, 0.53; 95% CI, 0.25-1.12; P = .62). Children with the R501X mutation (OR, 0.44; 95% CI, 0.22-0.88) were the least responsive to therapy. In a US cohort with AD, FLG null mutations were common. Children with FLG null mutations were more likely to have persistent AD. Although these mutations were more common in those of European ancestry, their effect on persistence was similar in those of African ancestry. Response to therapy was not uniform among children with FLG null mutations.